2007
DOI: 10.4269/ajtmh.2007.76.725
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods for Detecting the Eggs of Ascaris, Trichuris, and Hookworm in Infant Stool, and the Epidemiology of Infection in Zanzibari Infants

Abstract: Abstract. This study compared five methods for detecting the eggs of the human parasitic geohelminths Ascaris, Trichuris, and hookworm in infant stool, and describes the epidemiology of infection in infants from a parasite-endemic area. A total of 424 infants 5-11 months old were enrolled from three villages on Pemba Island, Zanzibar. Methods used included the Kato-Katz technique, formol ethyl acetate sedimentation, modified formol ethyl acetate sedimentation, modified Wisconsin floatation, and simple gravity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
2
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 21 publications
5
74
2
12
Order By: Relevance
“…The present study showed high prevalence of trichuriasis in the age group 10-15 yr among the school-age children. Our finding is consistent with those reported from other studies where researchers found higher prevalence in this age group (Narain et al Goodman et al 2007;Crowe et al 2014;Kattula et al 2014). However, Bundy et al (1987) reported high intensity infections in the age group 2-10 yr in a St. Lucian community.…”
Section: Discussionsupporting
confidence: 83%
“…The present study showed high prevalence of trichuriasis in the age group 10-15 yr among the school-age children. Our finding is consistent with those reported from other studies where researchers found higher prevalence in this age group (Narain et al Goodman et al 2007;Crowe et al 2014;Kattula et al 2014). However, Bundy et al (1987) reported high intensity infections in the age group 2-10 yr in a St. Lucian community.…”
Section: Discussionsupporting
confidence: 83%
“…Particularly in settings where the overall prevalences and intensities of helminth infections are low, for example after repeated rounds of chemotherapy, results obtained by the Kato-Katz method must be analysed with care. New data suggest that the Kato-Katz technique has drawbacks for screening stool samples from infants, as helminth infection intensities tend to be low and stool samples are more liquid than those collected from school-aged children or adults (Goodman et al, 2007). This issue is of considerable relevance, as recent studies suggest that infants and pre-school children are at higher risk of helminth infections and associated morbidity than previously assumed (Goodman et al, 2007;Stothard and Gabrielli, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of 988 stool samples from Malawi subjected to the Kato-Katz and ether concentration method revealed respective prevalences of 27.3% and 19.3% (Dacombe et al, 2007). Stool samples from 354 Zanzibari infants (aged 5-11 months) were examined by five different methods; the hookworm prevalence based on a duplicate Kato-Katz thick smear was 6.1%, whereas two ether concentration methods revealed prevalences of 5.0% and 5.8% (Goodman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This method is based on a protocol developed on Pemba for identifying diagnostic parasitic nematode stages in stool, when egg concentrations are expected to be low (Goodman et al, 2007). This protocol, when applied to stool samples where low concentrations of eggs and larvae are present, has proven to have greater or equal sensitivity to the sugar and flotation techniques commonly used to examine parasitic stages in soil.…”
Section: Methodsmentioning
confidence: 99%